Efeitos longitudinais do Programa Bolsa Família sobre indicadores socioeconômicos - Iara Azevedo Vitelli Viana (2024)
The study presented in this thesis aims to contribute to the discussion on the socioeconomic effects of social protection in Brazil in a multidimensional way. It starts with the Bolsa Família Program (PBF), as the Brazilian social protection floor, and then moves on to two studies, which are intertwined in their fundamental objectives, the socioeconomic development. The first study presents the effects of the PBF on the conclusion of primary and secondary education by two cohorts between 2010 and 2015 using multinomial logistic models. The second study presents the longitudinal effects of the PBF on the economy, as the municipal GDP, between 2009 and 2019, using Local Projection models. The results show positive effects of the PBF on the conclusion of the primary and secondary education by the beneficiaries and positive effects on the economy of Brazilian municipalities. Therefore, the PBF is a social protection program that has shown itself capable of making advances in two areas, interweaving social and economic effects and promoting an inclusive and persistent country development.